Incomprehensive Understanding About Mohammed: A Critic Over Orientalist - Sebayang, Deva Alvina (IAIN Surakarta, 2016)
This paper aims to reveal orientalism and how single story about Muhammad has been created. Single story created stereotype which containing the truth, but it was incomprehensive ways or unfinished story. According to Diechie, single story is a way to tell and portray something monolithically. Single story is related to tendency of human centered for seeing that she is better than other. There are no possibilities to look at the other as equal and connected with them. The other has assumed as an alien that is totally different and has no possibilities to be connected with them. This paper also describes debate between Edward Said and Bernard Lewis and Richard King about orientalism. These scholars are coming from different background but having shared point of view about orientalism.Keywords : single story, orientalism, Edward Said